2022
DOI: 10.1093/arclin/acac020
|View full text |Cite
|
Sign up to set email alerts
|

Functional Cognitive Disorder: Differential Diagnosis of Common Clinical Presentations

Abstract: Background Cognitive symptoms in the absence of neurological disease are common. Functional cognitive disorder (FCD) has been conceptualized as a cognitive subtype of functional neurological disorder. Although FCD is understood as different from exaggerated or feigned cognitive complaints, previous accounts have provided little practical advice on how FCD can be separated from factitious or malingered cognitive complaints. Also, the distinction of FCD from other medical or mental health disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 63 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…Studies have suggested that subjective reports of cognitive difficulties, including forgetfulness, distractibility, and retrieval problems, are frequent in patients with FNSD [58] . These deficits may be attributed to various factors, such as pain, fatigue, and excessive interoceptive monitoring, common in FNSD, which can negatively impact working memory, attention, and overall cognitive processing speed [59] . Further contributions to these subjective cognitive experiences may be perfectionism and the tendency to overinterpret cognitive impairments, both of which have been reported as clinical characteristics of FNSD [60] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have suggested that subjective reports of cognitive difficulties, including forgetfulness, distractibility, and retrieval problems, are frequent in patients with FNSD [58] . These deficits may be attributed to various factors, such as pain, fatigue, and excessive interoceptive monitoring, common in FNSD, which can negatively impact working memory, attention, and overall cognitive processing speed [59] . Further contributions to these subjective cognitive experiences may be perfectionism and the tendency to overinterpret cognitive impairments, both of which have been reported as clinical characteristics of FNSD [60] .…”
Section: Discussionmentioning
confidence: 99%
“…Although both conditions may involve subjective reports of cognitive challenges, FNSD encompasses a broader spectrum of neurological symptoms, including learning difficulties. Conversely, FCD presents a specific focus on cognitive problems such as forgetfulness and memory impairments [59] , [69] . However, given the considerable heterogeneity in the literature and methodological shortcomings, further research is warranted before dissociating the nature of cognitive difficulties in FNSD from those in FCD [58] .…”
Section: Discussionmentioning
confidence: 99%
“…Some symptoms (such as ‘tip-of-the-tongue’ hesitations in lvPPA [ 87 ]) are commonly experienced by normal speakers. Some patients presenting with health anxiety or functional cognitive disorder describe prominent speech and language symptoms: aside from lack of progression (and sometimes, abrupt onset), positive clues to these diagnoses on history include elaborate symptom descriptions and discrepancies between the severity of the subjective complaint and daily life performance [ 88 ]. On examination, hallmarks of a functional speech disorder include stuttering or prosodic changes (‘childlike’ or a ‘foreign accent’) with pronounced variability (severe disruption interspersed with segments of normal speech) and distractibility [ 89 ].…”
Section: How Can We Diagnose (And Track) Ppa Better?mentioning
confidence: 99%
“…Given features of internal inconsistency (i.e., report of severe memory trouble yet evidence of intact memories and self-reported daily living activities in interview), we communicated a diagnosis of functional cognitive disorder (FCD), a type of FND, to the patient and her partner. [1][2][3] We discussed that this condition is common and that treatments are available. We also pointed out that there was likely no overt structural damage, and that there was a possibility for improvement.…”
Section: Adjunctive Workup and Diagnosismentioning
confidence: 99%